HEAR THEM OUT: CONSTRAINTS ENCOUNTERED BY IELTS STUDENTS IN THE WRITING CLASS - Tiara Cita Maharani; Sri Setyarini (Edusentris, 2020)
The purpose in this study is to investigate the problems faced by the students in the IELTS writing class and how the teacher addressed the existing problems. It employed a qualitative narrative inquiry design since the researcher took the role as the teacher in the preparation class. The participants were three senior high school students who enrolled in an IELTS preparation class at one of the private English language learning centres in Bandung. The data were collected through in-depth interviews with the participants, classroom observations including my teaching journal, and the students’ writing. The study revealed that limited vocabulary, difficulties in constructing ideas, insufficient mechanical writing aspects, boredom, exhaustion, anxiety, and language barrier were the challenges encountered by the participants. Moreover, among a number of teaching strategies that I conducted to address the problems, drilling IELTS writing strategies and giving personal feedback to the participants were considered to be the most effective since they gained positive responses from the participants in which they managed to demonstrate improvement on their IELTS writing skills.